(untitled) (Research, Society and Development, 2020)
The present study was carried out with the objective of estimating the microbial protein synthesis through the urinary excretion of purine derivatives in Santa Ines sheep fed with dehydrated brewery residue in the proportions of 0; 20; 40; 60 and 80% of inclusion in the concentrated portion of the ration. Thirty-five Santa Ines lambs were used, with an average initial body weight of 16.00 ± 1.69 kg and approximately 70 days of age, evaluated in a completely randomized design, with five experimental rations and seven replicates. The lambs’ urine samples were obtained using the spot collection technique. The daily excretion of purine derivatives, expressed in mmol/day, presented for allantoin and total purines, a decreasing linear effect (P<0.05). However, for uric acid, there was no interference from the inclusion of dehydrated brewery residue (P>0.05). The daily absorption of microbial purines, expressed in mmol/day, showed a decreasing linear effect (P<0.05) as the dehydrated brewery residue was added to the ration. The efficiency of microbial protein synthesis, expressed in g/kg, for microbial nitrogen (N) and microbial crude protein (CP) by digestible organic matter consumed, by digestible organic matter apparently fermented in the rumen and by total digestible nutrients consumed were not influenced (P>0.05) by including dehydrated brewery residue in the concentrated portion of the ration. The dehydrated brewery residue, when included up to 80% in the concentrated portion of Santa Ines lambs’ rations, does not influence the microbial protein synthesis.